2022
DOI: 10.1093/oncolo/oyac106
|View full text |Cite
|
Sign up to set email alerts
|

The Value of In Vivo Reflectance Confocal Microscopy as an Assessment Tool in Chemotherapy-Induced Peripheral Neuropathy: A Pilot Study

Abstract: Background There is a lack of standardized objective and reliable assessment tools for chemotherapy-induced peripheral neuropathy (CIPN). In vivo reflectance confocal microscopy (RCM) imaging offers a non-invasive method to identify peripheral neuropathy markers, namely Meissner’s corpuscles (MC). This study investigated the feasibility and value of RCM in CIPN. Patients and Methods Reflectance confocal microscopy was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…This might be explained by the slightly different location of the investigated region because QST was measured on the back of the hand and at the base of the thumb, depending on the QST parameter. In other studies, a loss of Meissner corpuscles correlated with mechanical, vibration, or thermal thresholds in QST, 16,45 but there is no clear assignment of Meissner corpuscles to a specific tactile quality.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This might be explained by the slightly different location of the investigated region because QST was measured on the back of the hand and at the base of the thumb, depending on the QST parameter. In other studies, a loss of Meissner corpuscles correlated with mechanical, vibration, or thermal thresholds in QST, 16,45 but there is no clear assignment of Meissner corpuscles to a specific tactile quality.…”
Section: Discussionmentioning
confidence: 80%
“…Miswiring of Meissner corpuscles after nerve injury in preclinical models by sprouting nociceptors could explain tactile allodynia caused by light touch. 22 Multiple studies described reduced Meissner corpuscles in other pain conditions, including diabetic, HIV, and chemotherapy-induced neuropathy, 11 , 16 , 23 , 42 , 45 but only one study investigated Meissner corpuscles in CRPS. 2 The authors showed disorganized Meissner corpuscles with disruption of Aβ-innervation in skin samples from amputated extremities of 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given limitations around CCM, some are looking for alternative PN biomarkers. Reflective confocal microscopy, for example, is a relatively new technology that measures the density of Meissner corpuscles in patients' fingertips and may be used to identify various forms of PN [8].…”
Section: Objective Techniquesmentioning
confidence: 99%
“…While estimates vary widely by diagnostic criteria and population studied, PN likely affects between 21% and 50% of patients with HIV or diabetes during the course of their disease, a significant proportion of patients with pre-diabetes, and at least 40% of patients exposed to neurotoxic chemotherapeutic agents. PN may also be idiopathic [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%